Altered hippocampal microstructure and function in children who experienced Hurricane Irma. Issue 5 (16th December 2020) - Conley, May I.; Skalaban, Lena J.; Rapuano, Kristina M.; Gonzalez, Raul; Laird, Angela R.; Dick, Anthony Steven; Sutherland, Matthew T.; Watts, Richard; Casey, B.J.
Abstract: Hurricane Irma was the most powerful Atlantic hurricane in recorded history, displacing 6 million and killing over 120 people in the state of Florida alone. Unpredictable disasters like Irma are associated with poor cognitive and health outcomes that can disproportionately impact children. This study examined the effects of Hurricane Irma on the hippocampus and memory processes previously related to unpredictable stress. We used an innovative application of an advanced diffusion‐weighted imaging technique, restriction spectrum imaging (RSI), to characterize hippocampal microstructure (i.e., cell density) in 9‐ to 10‐year‐old children who were exposed to Hurricane Irma relative to a non‐exposed control group (i.e., assessed the year before Hurricane Irma). We tested the hypotheses that the experience of Hurricane Irma would be associated with decreases in: (a) hippocampal cellularity (e.g., neurogenesis), based on known associations between unpredictable stress and hippocampal alterations; and (b) hippocampal‐related memory function as indexed by delayed recall. We show an association between decreased hippocampal cellularity and delayed recall memory in children who experienced Hurricane Irma relative to those who did not. These findings suggest an important role of RSI for assessing subtle microstructural changes related to functionally significant changes in the developing brain in response to environmental events.